2020
DOI: 10.1308/rcsann.2019.0156
|View full text |Cite
|
Sign up to set email alerts
|

Association between thyroid nodule size and malignancy rate

Abstract: Introduction The diagnostic performance of ultrasound-fine needle aspiration to identify thyroid nodules harbouring malignancy remains variable. The aim of this study was to determine thyroid nodule size and cytological classification as predictors of malignancy risk. Materials and methods We conducted a retrospective cohort analysis at an academic hospital involving 499 consecutive patients who underwent thyroid surgery between 2004 and 2015. Results A total of 503 thyroid nodules (499 patients, 84% female; m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…These results agree with Jinih et al [28] who reported that, their results suggested that, nodule size is not accurately predict the risk of thyroid malignancy irrespective of the results of FNAC.…”
Section: Discussionsupporting
confidence: 91%
“…These results agree with Jinih et al [28] who reported that, their results suggested that, nodule size is not accurately predict the risk of thyroid malignancy irrespective of the results of FNAC.…”
Section: Discussionsupporting
confidence: 91%
“…In some studies, thyroid nodule size was found to be inversely related to malignancy risk, as larger nodules have lower malignancy rates (31,32). However, this has been contested by other studies (33,34). The 2015 ATA guideline and 2017 ACR Thyroid Imaging Reporting and Data System (TI-RADS) recommend diagnostic fine-needle aspiration (FNA) of the thyroid nodule based on nodule size and features of high-risk imaging on ultrasound, such as microcalcification, nodule hypoechogenicity, solid component, irregular margin, and a taller-than-wide shape (7,9).…”
Section: Discussionmentioning
confidence: 99%
“…Though some studies found that malignant risk is associated with nodule size, for example, a series of observational studies have found that thyroid cancers over 4 cm were associated with more aggressive behavior whereas tumors smaller than 1.5 cm had a good overall prognosis [12,13,14]. However, some other researches indicated no correlation between size and risk [15,16]. A recent study found that the impact of nodule size on the malignancy risk differed according to the ultrasound pattern.…”
Section: Discussionmentioning
confidence: 99%
“…More ultrasound-found nodules were diagnosed as carcinoma by histology examinations [136 (11.2%) nodules found by ultrasound vs 68 (3.9%) by palpation, x 2 =59.737, p=0.000], and 88 (64.7%) nodules found by ultrasound were non-microcarcinoma. Among the malignant nodules con rmed by histopathology, a higher proportion of microcarcinoma was detected in ultrasound-found nodules [35.3% (48/136) vs 16.2% (11/68), x 2 =8.183, p=0.004].…”
Section: Introductionmentioning
confidence: 99%